Identification and classification of digital green innovation based on interaction Maclaurin symmetric mean operators by using T-spherical fuzzy information - Hou, Xiaona; Naseem, Areeba; Ullah, Kifayat; Naeem, Muhammad; Akram, Maria; Yin, Shi (Frontiers in Environmental Science, 2023)
Digital Green concept refers to the devotion to digital technology, techniques, of procedures in the area of ecological or sustainable conservation. It contains leveraging digital techniques, procedures, and new tools to evaluate environmental problems and promote sustainable development. The major influence of this article is to evaluate the selection of the best digital green technology, for this, we aim to propose the idea of Maclaurin Symmetric mean (MSM) operators based on interaction operational laws for T-spherical fuzzy (TSF) information, such as TSF interaction weighted averaging (TSFIWA), generalized TSF interaction weighted averaging (GTSFIWA), TSF interaction weighted geometric averaging (TSFIWGA), TSF interaction MSM (TSFIMSM), TSF interaction Bonferroni mean (TSFIBM), and TSF interaction weighted Maclaurin symmetric mean (TSFIWMSM) operators. Some dominant and reliable properties are also invented for evaluated work. Moreover, to address the best digital green innovation among the top five digital green innovations, we illustrate the procedure of the multi-attribute decision-making (MADM) technique under the presence of the derived operators. Finally, we demonstrate a numerical example for evaluating the comparative study between proposed and existing or prevailing operators to enhance the worth of the derived theory.